Biasing a ferronematic – a new way to detect weak magnetic field. Issue 26 (14th June 2016) - Tomašovičová, Natália; Kováč, Jozef; Raikher, Yuriy; Éber, Nándor; Tóth-Katona, Tibor; Gdovinová, Veronika; Jadżyn, Jan; Pinčák, Richard; Kopčanský, Peter
Abstract : The magnetic properties of a ferronematic are studied. A dc magnetic field applied in the isotropic phase causes an irreversible change of the ac magnetic susceptibility at the phase transition. Abstract : The magnetic properties of a ferronematic, i.e., a nematic liquid crystal doped with magnetic nanoparticles in low volume concentration are studied, with the focus on the ac magnetic susceptibility. A weak dc bias magnetic field (a few Oe) applied to the ferronematic in its isotropic phase increases the ac magnetic susceptibility considerably. Passage of the isotropic-to-nematic phase transition resets this enhancement irreversibly (unless the dc bias field is applied again in the isotropic phase).